2007
DOI: 10.1002/ca.20567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods to reduce formaldehyde levels of cadavers in the dissection laboratory

Abstract: Dissection of conventionally embalmed cadavers exposes students, staff, and faculty to formaldehyde, a probable carcinogen. Therefore, prudent practices should seek to minimize formaldehyde exposure. In this study, we evaluated two commercially available chemicals, InfuTrace and Perfect Solution, for their effectiveness in reducing ambient formaldehyde levels. Four cadavers embalmed conventionally with formaldehyde and/or with the above agents were compared for their formaldehyde levels under conditions that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 10 publications
0
41
0
2
Order By: Relevance
“…7 Airborne formaldehyde is the most harmful volatile chemical among those included in the present study and has the strictest biohazard security control codes. 3,7,19,22 Many institutions and government regulations have considered it to be a carcinogenic agent. 3,5,7,10,11,15,19,22 Although formaldehyde is still needed to prevent microorganism growth (especially fungi), formaldehyde content in the customized embalming fluid described here was almost 80% less than in a conventional formaldehyde mixture.…”
Section: Biohazard Risk and Health Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Airborne formaldehyde is the most harmful volatile chemical among those included in the present study and has the strictest biohazard security control codes. 3,7,19,22 Many institutions and government regulations have considered it to be a carcinogenic agent. 3,5,7,10,11,15,19,22 Although formaldehyde is still needed to prevent microorganism growth (especially fungi), formaldehyde content in the customized embalming fluid described here was almost 80% less than in a conventional formaldehyde mixture.…”
Section: Biohazard Risk and Health Standardsmentioning
confidence: 99%
“…Additionally, many studies have reported that long-term exposure to high airborne formaldehyde concentrations in the laboratory is hazardous. 6,9,10,11,15 In 2006, the International Agency for Research on Cancer (IARC) 22 and the US Environmental Protection Agency 19 classified formaldehyde as a probable human carcinogen.…”
mentioning
confidence: 99%
“…Selected studies have shown that the levels of airbone FA in anatomy laboratories exceed recommended exposure criteria 0.05 ppm limit (3, 9,10,11,12,19,23,25,26,27,28,29,31,32,33). These are primarily caused by evaporation of formaldehyde used for the preservation of tissues and specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers evaluated two chemicals, InfuTrace and Perfect Solution, for their effectiveness in reducing ambient formaldehyde levels (26).…”
Section: Environmental Monitoring and Preventive Measures Reducing Thmentioning
confidence: 99%
“…화 학적 특성과 차이를 넘어서 방부액은 장기 및 조직이 원래 의 색깔을 유지해야 하고 과도하게 경화되는 것을 방지하 는 등 오랜 기간 동안 구조적 보존이 가능해야 한다 [13]. [19], 이소프로판올 (isopropanol) [20], 메탄올 (methanol) [21], 페녹시에탄올 (phenoxyethanol) [22] 과 상품으로 시판 중인 고정액 [23,24] (Table 2). (Fig.…”
unclassified